OVERCOMING SOCIAL DIFFERENTIATION AS A FACTOR IN THE TRANSITION TO SUSTAINABLE ECONOMIC GROWTH - P. V. Arefyev (Финансы: теория и практика, 2017)
In 1970s of XX century, many prominent economists and environmentalists reflected about the limits of economic growth and opposed to the concept of economic growth the concept of sustainable harmonious economic development which implies that investment directions, orientation of scientific and technological revolution and exploitation of natural resources would be consistent with each other to strengthen the current and future potential to meet human needs. Meanwhile, the fact that in the 30s of XX century the United States undertook an unprecedented experiment for implementing the New Deal policy of FD Roosevelt seems to be completely overlooked. The New Deal, on the one hand, slowed the pace of economic recovery and economic growth in the U.S., but on the other hand, it resulted in reduction of social differentiation, increased the share of the middle class and contributed to sustainable development of the country. The social sphere in Russia is largely a relic of the old socialist system of etatism.. The existing social system in the country is a powerful barrier to economic development. Therefore, we are particularly interested in the experience of the United States.